Alfabetização financeira dos estudantes do ensino médio de instituições públicas - Souza, Gladistone Cosme de (2023)
This research aimed to verify the level of financial literacy of high school students from public institutions in the city of Ituiutaba/MG, and specifically to analyze the association between the level of financial literacy and socioeconomic and demographic factors. For this, a questionnaire was applied directly to a sample of 93 high school students from different public institutions. After applying the questionnaire, the data were analyzed using descriptive statistics and correlation, normality and comparison tests between groups. The results showed that, for the most part, students have good financial behavior and attitude, however, they are not well financially literate, according to the rates achieved by respondents in this regard. It was also noted the lack of financial knowledge on the part of the students since only approximately 2% reached a score above 50 in this item. The results are useful as they indicate the need for educational institutions to establish actions and/or educational strategies that contribute to the financial literacy of high school students in the area covered by the study, suggesting revisiting the curricula of disciplines whose content is associated whether directly or indirectly to finance learning. Therefore, it is expected that the research results contributed directly and indirectly to society in general, since financially literate individuals tend to efficiently manage money, both in the personal and family context, as well as in the business environment.